Do lakes feel the burn? Ecological consequences of increasing exposure of lakes to fire in the continental United States. (13th July 2019) - McCullough, Ian M.; Cheruvelil, Kendra Spence; Lapierre, Jean‐François; Lottig, Noah R.; Moritz, Max A.; Stachelek, Jemma; Soranno, Patricia A.
Abstract: Wildfires are becoming larger and more frequent across much of the United States due to anthropogenic climate change. No studies, however, have assessed fire prevalence in lake watersheds at broad spatial and temporal scales, and thus it is unknown whether wildfires threaten lakes and reservoirs (hereafter, lakes) of the United States. We show that fire activity has increased in lake watersheds across the continental United States from 1984 to 2015, particularly since 2005. Lakes have experienced the greatest fire activity in the western United States, Southern Great Plains, and Florida. Despite over 30 years of increasing fire exposure, fire effects on fresh waters have not been well studied; previous research has generally focused on streams, and most of the limited lake‐fire research has been conducted in boreal landscapes. We therefore propose a conceptual model of how fire may influence the physical, chemical, and biological properties of lake ecosystems by synthesizing the best available science from terrestrial, aquatic, fire, and landscape ecology. This model also highlights emerging research priorities and provides a starting point to help land and lake managers anticipate potential effects of fire on ecosystem services provided by fresh waters and their watersheds. Abstract : Wildfires are becoming larger and more frequent across much of the United States. We show that fire activity has increased in lake watersheds across the continental United States from 1984 to 2015, particularly since 2005. Despite over 30 years of increasing exposure, fire effects on lakes have not been well studied. We propose a conceptual model of how fire may influence the physical, chemical, and biological properties of lakes. This model highlights emerging research priorities and provides a starting point to help land and lake managers anticipate potential effects of fire on ecosystem services provided by lakes and their watersheds.